Measuring International Skilled Migration: New Estimates Controlling for Age of Entry - Michel Beine; Frederic Docquier; Hillel Rapoport (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2006)
Recent data on international skilled migration define skilled migrants according to education level independently of whether education has been acquired in the home or in the host country. In this paper we use immigrants' age of entry as a proxy for where education has been acquired. Data on age of entry are available from a subset of receiving countries which together represent more than 3/4 of total skilled immigration to the OECD. Using these data and a simple gravity model, we estimate the age-of-entry structure of skilled immigration and propose alternative brain drain measures by excluding those arrived before age 12, 18 and 22. The results for 2000 show that on average, 68% of the global brain drain is accounted for by emigration of people aged 22 or more upon arrival (78% and 87% for the 18 and 12 year old thresholds, respectively). For some countries this indeed makes a substantial difference. However, cross-country differences are globally maintained, resulting in extremely high correlation levels between corrected and incorrected rates. Similar results are obtained for 1990.
Keywords: 330